Assassins against the old order : Italian anarchist violence in Fin de Siècle Europe - Pernicone, Nunzio, 1940-2013; Ottanelli, Fraser M. (University of Illinois Press, 2018)
"Assassins against the Old Order delves into the history of Italian anarchist violence and sets out to understand the causes and general conditions that led to it. Despite a proliferation of new studies on anarchism, anarchist violence and its main school of thought--"propaganda of the deed"-- remain generally understudied and misunderstood. Misconceptions about anarchism in general, and anarchist violence in particular, have dominated public discourses and popular culture from its inception. Anarchists were quickly and conveniently branded as a "demonic menace to society" - a view that was reinforced by the period's pseudo-scientific criminologist theories as well as sensationalist accounts of the fin-de-siècle political assassinations which were framed as part of a presumed terrorist anarchist conspiracy to overthrow the established order. This book provides a cutting-edge synthesis of the intellectual origins, milieu and nature of Italian anarchist violence as well as a fascinating portrait of its major players"--